2022
DOI: 10.22541/au.166573612.23507910/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogeographic analysis of Siraitia grosvenorii in subtropical China provides insight into the origin of cultivated monk fruit and conservation of genetic resources

Abstract: Siraitia grosvenorii, an economically important plant species with high medicinal value, is endemic to subtropical China. To determine the population structure and origin of cultivated S. grosvenorii, we examined the variation in three chloroplast DNA regions (trnR-atpA, trnH-psbA, trnL-trnF) and two nuclear gene orthologs (CHS and EDL2) of S. grosvenorii in 130 individuals, selected from 13 wild populations across its natural distribution range, and 21 cultivated accessions using a phylogeographic approach. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Through the study of Siraitia grosvenorii plant cultivation using plant bioreactor, proliferation rate, shoot length, fresh and dry weight Indications of proliferation rate, shoot length, fresh weight, and dry weight showed that the total biomass of roselle cultivated in plant bioreactor was significantly higher than in solid and liquid cultivation (Shivani et al, 2021). The reactor promoted the growth and quality of S. grosvenorii seedlings, and the natural‐like plant S. grosvenorii obtained may have a positive effect on isolated rooting and transplanting in large‐scale commercial production (Xie et al, 2023). Some researchers evaluated Vanilla planifolia in solid culture, partial submergence and plant bioreactor for shoot proliferation efficiency and found that compared to solid culture, the proliferation rate in the reactor increased by a factor of three (Yeh et al, 2021).…”
Section: The Effect Of Thz Radiation On the Growth Process Of Pinelli...mentioning
confidence: 99%
“…Through the study of Siraitia grosvenorii plant cultivation using plant bioreactor, proliferation rate, shoot length, fresh and dry weight Indications of proliferation rate, shoot length, fresh weight, and dry weight showed that the total biomass of roselle cultivated in plant bioreactor was significantly higher than in solid and liquid cultivation (Shivani et al, 2021). The reactor promoted the growth and quality of S. grosvenorii seedlings, and the natural‐like plant S. grosvenorii obtained may have a positive effect on isolated rooting and transplanting in large‐scale commercial production (Xie et al, 2023). Some researchers evaluated Vanilla planifolia in solid culture, partial submergence and plant bioreactor for shoot proliferation efficiency and found that compared to solid culture, the proliferation rate in the reactor increased by a factor of three (Yeh et al, 2021).…”
Section: The Effect Of Thz Radiation On the Growth Process Of Pinelli...mentioning
confidence: 99%
“…The strict molecular clock model was used as the basic model for branch rates implemented in BEAST (Zuckerkandl & Pauling, 1965), which can be calibrated by setting a substitution rate or dates of specific nodes or node sets (Drummond & Rambaut, 2007). In this study, we used the strict molecular clock model and the GTR + G + I model with four Gamma categories.…”
Section: Sequence Analysismentioning
confidence: 99%